UTILIZING DISCOURSE MULTY REPRESENTATION MODEL WITH KELUBANG TARIF MEDIA TO ENHANCE PROBLEM SOLVING ABILITY - Delfira Anggraeni C.T; Henry Suryo Bintoro; Jayanti Putri Purwaningrum (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this study was to determine the difference in the improvement of students’ mathematical problem-solving ability between those who utilized the Discourse Multi Representation model with Kelubang Tarif media and those who applied the expository model. This quasi-experimental study was conducted at an elementary school in Kudus. The population consisted of all fourth-grade students in the school, and the samples were two classes selected using purposive sampling. This study employed a nonequivalent pretest-posttest control group design. The instrument used was a test to measure students' mathematical problem-solving abilities, and the data were analyzed using descriptive quantitative techniques. The N-Gain test was employed to examine the results. The findings indicated that there was a significant difference in the improvement of mathematical problem-solving ability between students who learned using the Discourse Multi Representation model with Kelubang Tarif media and those who learned using the expository model. Thus, the Discourse Multi Representation model with Kelubang Tarif media can be used as an effective alternative in mathematics learning to enhance students’ problem-solving skills.